2017
DOI: 10.3329/medtoday.v29i1.33851
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Surgical Site Infection between Laparoscopic Appendectomy and Open Appendectomy

Abstract: Surgical site infection (SSI) is defined as infection at surgical site within 01 month after surgery (or within a year in case of implant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Since then, numerous studies have demonstrated that the laparoscopic method as the high success ratio and less rate of complications in the majority of instances with appendicitis. LA has less wound infection risk than OA 20 . Pre-operative intravenous antibiotics have been found to lower the incidence of post-operative SSIs, regardless of the surgical strategy adopted.…”
Section: Discussionmentioning
confidence: 95%
“…Since then, numerous studies have demonstrated that the laparoscopic method as the high success ratio and less rate of complications in the majority of instances with appendicitis. LA has less wound infection risk than OA 20 . Pre-operative intravenous antibiotics have been found to lower the incidence of post-operative SSIs, regardless of the surgical strategy adopted.…”
Section: Discussionmentioning
confidence: 95%
“…In a study on appendectomy wounds, Salim et al . [ 25 ] also reported the predominance of S. aureus. It is possible that the application of TCS in the fascia plane might have prevented the migration of enteric bacteria from deeper layers into the subcutaneous plane but did little in preventing S. aureus which is a skin commensal and is also found in the nares of health workers from colonising the wound from without.…”
Section: Discussionmentioning
confidence: 99%